Implementasi Program Bantuan Langsung Tunai Bagi Masyarakat Miskin di Desa Urung Purba Kecamatan Purba Kabupaten Simalungun - Purba, Jaya Govindo; Suharyanto, agung; Lubis, Khairunnisah (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2024)
This article or writing aims to describe the implementation of the Direct Cash Assistance (BLT) program which has been carried out in Urung Purba Village, Purba District, Simalungun Regency, as well as identifying inhibiting factors in its implementation. The problem focused on the Implementation of the Direct Cash Assistance Program, to approach this problem, a theoretical reference from Edward III's theory of policy implementation is used, which has 4 indicators, namely communication, resources, disposition, and bureaucratic structure. Data was collected through data collection techniques through observation, interviews, and documentation and analyzed qualitatively. This study concluded that the implementation of the Direct Cash Assistance (BLT) Program in Urung Purba Village showed positive results through effective communication between village officials and aid recipients. Even though human resources are fully involved in distribution, the quality still needs to be improved. The friendly disposition of implementers supports community acceptance, and the bureaucratic structure is by SOPs. However, obstacles such as a shortage of data collectors and unequal distribution of aid create social synchronization, especially due to less-than-optimal data collection systems and oligarchic practices. Improvements in resource management and data collection systems are needed to improve the situation.